Knowledge and practice of COVID-19 pandemic prevention in a community in Jakarta - Wahid, Mardiastuti H; Kiranasari, Ariyani; Ningsih, Ika; Sari, Meutia Kumala; Aziz, Mochamad Helmi (Indonesian Society for Clinical Microbiology (Perhimpunan Dokter Spesialis Mikrobiologi Klinik Indonesia), 2024)
Introduction: COVID-19 is an emerging infectious disease that causes a pandemic with high morbidity and mortality due to its wide transmission. This situation should be prevented not only by the government but also by the community. Efforts have taken place to prevent COVID-19 transmission including the obligation to wear masks, wash hands, keep a distance, stay at home, avoid crowds, and administer the vaccination. This study aims to examine the communities’ knowledge, perception, and practice in preventing the spread of the COVID-19 pandemic. Methods: This is a descriptive cross-sectional study in a suburban area in Jakarta. Ninety-seven respondents participated in this study. Data was collected by filling questionnaire via G-form and analyzed descriptively. Results: A total of ninety-seven respondents participated in this study with aged 18-73 years. In terms of knowledge about COVID-19, the majority of the respondents know the etiology, symptoms, transmission, and the way to prevent the disease. Only less than half of them understand that corpses are capable of transmitting COVID-19. However, this research found a lack of implementation of practice in preventing COVID-19 transmission because only 62.9% of respondents always bring hand sanitizer/ABHS. Only a small percentage change clothes after leaving the house, do exercise, and take vitamins. Conclusion: Although the community has sufficient knowledge and a good perception of COVID-19 prevention, rigorous effort should be provided to enhance the quality of practice of the community, to prevent the spread of COVID-19.